PERCEPTUAL AWARENESS OF SOCIAL STUDIES TEACHER CANDIDATES REGARDING THE VALUES WITHIN THE CURRICULUM - Çağrı ÖZTÜRK DEMİRBAŞ (Fırat University, 2019)
In the study, perceptual awareness of social studies teacher candidates regarding the values within the social studies curriculum has been analyzed. The working group of the study is composed of 71 social studies teacher candidates in total, 36 female (50.7%) and 35 males (49.3%), receiving education at Ahi Evran University. The study is qualitative, consisting of an interview form structured as open-end questions. Content analysis has been used in analyzing the data obtained within the scope of the study and the mentioned data were collected in June 2011. Perceptual awareness of prospective teachers regarding the value concept has been discussed under four main categories, in order to determine their opinions on teaching value. These four categories are respectively as follows; value-centered expressions (42.3% valuist), society-centered expressions (22.5% socialist), in